The Future of Work in India: Adapting to the Fourth Industrial Revolution - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
Since 1991, India has undergone a series of economic reforms that have accelerated its integration into the global economy. Reduced trade barriers, removal of barriers to foreign investment, and simplified regulations helped bring India into an age of rapid, service sectorled growth. However, the gains from this breakout have not reached every Indian. Inequality continues to widen, as a freer market has exacerbated existing class divisions in income, wealth, and access to skills and capital. These social challenges have been the hallmarks of India's transition into the digital economy, in which ICTs have enabled commerce and opportunity to pour in from around the globe at the cost of opportunity and social mobility for India's most excluded citizens. Inequality and social prejudices prevent these groups from gaining the literacies and technical competencies necessary to participate in the formal sector of this new economy. For more than 80 percent of workers without access to formal employment, a shadowy and unproductive informal sector remains as the only source of income, testifying to a much higher rate of unmeasured unemployment among those seeking to profit to the fullest from their abilities in a way that headline statistics do not show. As India has continued its transition into the digital economy, a new technological revolution is starting which, in the long term, will revolutionize the future of work and the nature of the economy. In the modern digital economy, machines are capable of automating simple and predictable tasks, but humans fill in to bring the nuance, complexity and creativity our technology cannot yet provide. Yet new advances in computing power, the growing ubiquity of internet-connected devices, and algorithms which mimic the cognitive processes of human thought are building a world in which complex and unpredictable processes can be automated through the sheer weight of predictive data. In the process, work tasks currently seen as reserved for humans can increasingly be ceded to machines, threatening to upend paradigms of employment in place throughout human history. (...)
Keywords: 330